MANIFESTASI IDEOLOGI ROMANTIK DALAM PUISI-PUISI ACEP ZAMZAM NOOR - Efsa, Nita Widiati (LITERA, 2015)
Abstract This study aims to describe the romantic ideology manifestation in Acep Zamzam Noor’s poems, in terms of: (a) romantic feelings, (b) romantic nature, (c) romantic imagination, and (d) romantic mythology. The data sources were ten poetry anthologies by Acep Zamzam Noor (AZN) that were published in 1982-2007. The data analysis steps were: (a) reading and checking the selected data, (b) marking and classifying data, and (c) analyzing data based on relevant theories, namely those of new historicism, archeological knowledge, and psychology of religion. The research findings are as follows. First, the romantic ideology manifestation related to feelings comprises: (a) longing, (b) loneliness, (c) anxiety, and (d) death. Second, the romantic ideology manifestation related to nature includes: (a) sea, (b) mountain, and (c) sky. Third, the romantic ideology manifestation related to imagination comprises: (a) production imagination and (b) reproduction imagination. Fourth, the romantic ideology manifestation related to mythology includes: (a) religious myth, (b) ritual myth, (c) historical myth, (d) erotic myth, and (e) political myth. Keywords: ideology manifestation, romantic ideology, feelings, nature, imagination, mythology